The Impact of Evaluation of Regulatory Controls in The Cost of Governance - Yacoub Ishaq Mahdi, Maryam; Subhi Abdulhussein Aljeboori, Azher (Iraqi Journal for Administrative Sciences, 2026)
This research aims to measure the impact of evaluating of regulatory controls in the cost of governance within the Iraqi commercial banking sector. The research population consisted of internal auditors in the Iraqi commercial banking sector, and a sample of 14 banks was selected. A questionnaire was used as the primary data collection tool from the selected banks. The questionnaire comprised two sections: the first addressed the evaluation of regulatory controls through three dimensions: regulatory control efficiency, regulatory control suitability, and regulatory controls effectiveness. The second section addressed the cost of governance through three dimensions: agency costs, compliance costs, and control costs. This provided a methodology for measuring the impact. A total of 189 employees from these banks participated in the survey, which was distributed to them both in person and electronically. All questionnaires were valid, and the data were analyzed using the SPSS version 26 statistical software. The research concluded that there is an effective impact of evaluating regulatory controls on the cost of governance, and this impact contributes to reducing the cost of governance. In light of the conclusions, the researcher presented several recommendations, the most important of which is the need to adopt an approach that links the evaluation of regulatory controls to the cost of governance, with the aim of achieving a sustainable reduction in the cost of governance.